PENGARUH TRANSFORMASI SUHU TERHADAP PEMADATAN AGREGAT BATU GAMPING PADA CAMPURAN ASPAL PANAS (HOTMIX) ASPHALT CONCRETE WEARING COURSE (AC-WC) TERHADAP KARAKTERISTIK MARSHALL - Febriansyah, Dani; Hamzah, Yayu Sriwahyuni (Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Road pavement layers are an important part of road construction that supports traffic loads. Where the layer must be able to spread stress, not experience changes in shape and have sufficient stability. One alternative filler material that can be used in asphalt concrete mixtures is Madurese white brick powder, because Madurese white limestone powder is a local additive that is widely available in Madura.. The temperature transformation used is 160°C/146°C, 170°C/156°C, 180°C/166°C, 190°C/176°C, 200°C/186°C with an asphalt content of 5.2 %, 5.7%, 6.2%. The test uses the Marshall test method by looking for Marshall characteristics. This research aims to determine the effect of mixing temperature transformation and compaction of AC-WC hot asphalt using limestone and gold in Sampang District, Sampang Regency. Based on the results of the marshall quoient test, the marshall characteristics almost meet all classifications, namely stability of 1746 kg, flow with a result of 3.5 mm, marshall qouient with a value of 362.89 kg/mm ​​and VMA of 22.40%, while VIM and VFB do not yet meet classification, namely for VIM of 12% which according to classification should be >65%.